2014
DOI: 10.3758/s13428-014-0483-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between motivation, monetary compensation, and data quality among US- and India-based workers on Mechanical Turk

Abstract: In this study, we examined data quality among Amazon Mechanical Turk (MTurk) workers based in India, and the effect of monetary compensation on their data quality. Recent studies have shown that work quality is independent of compensation rates, and that compensation primarily affects the quantity but not the quality of work. However, the results of these studies were generally based on compensation rates below the minimum wage, and far below a level that was likely to play a practical role in the lives of wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
200
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(209 citation statements)
references
References 22 publications
6
200
3
Order By: Relevance
“…Mason and Watts [29] found that paying workers more increased the number of tasks workers chose to complete, but did not increase performance on each task. That increased pay did not increase performance was observed by other authors as well [4,10,25,30]. In this paper, we found that paying workers more can actually increase their performance for some types of tasks.…”
Section: Introductionsupporting
confidence: 74%
“…Mason and Watts [29] found that paying workers more increased the number of tasks workers chose to complete, but did not increase performance on each task. That increased pay did not increase performance was observed by other authors as well [4,10,25,30]. In this paper, we found that paying workers more can actually increase their performance for some types of tasks.…”
Section: Introductionsupporting
confidence: 74%
“…When they entered the code into a textbox on the MTurk website, they were paid 20 cents. Litman, Robinson, and Rosenzweig (2015) showed that compensation in this range is sufficient to ensure high quality data in both the USA and India.…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…In India, 65% of turkers are male, the average age is 30.5 years, and 81% have a college education (19). Making money is the top motivation for using Mechanical Turk, ahead of other factors such as enjoyment and killing time (20). Evidence regarding the influence of compensation rates is conflicting; early work suggested that low compensation rates (on average $1.60/h) did not affect the quality of completed tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence regarding the influence of compensation rates is conflicting; early work suggested that low compensation rates (on average $1.60/h) did not affect the quality of completed tasks. However, a recent study found that although compensation did not influence quality for US turkers, turkers from India produced higher quality data for higher compensation (20). Turkers have been used in health-related studies and can be useful in research given their low pricing and speed of service (21).…”
Section: Introductionmentioning
confidence: 99%